THADA regulates the organismal balance between energy storage and heat production - Moraru, Alexandra; Çakan Akdogăn, Gülçin; Straßburger, Katrin; Maleš, Matilda; Müller, Sandra; Jabs, Markus; Mülleder, Michael; Frejno, Martin; Braeckman, Bart P.; Ralser, Markus; Teleman, Aurelio A. (Developmental cell, 2017)
Summary Human susceptibility to obesity is mainly genetic, yet the underlying evolutionary drivers causing variation from person to person are not clear. One theory rationalizes that populations that have adapted to warmer climates have reduced their metabolic rates, thereby increasing their propensity to store energy. We uncover here the function of a gene that supports this theory. THADA is one of the genes most strongly selected during evolution as humans settled in different climates. We report here that THADA knockout flies are obese, hyperphagic, have reduced energy production, and are sensitive to the cold. THADA binds the sarco/ER Ca2+ ATPase (SERCA) and acts on it as an uncoupler. Reducing SERCA activity in THADA mutant flies rescues their obesity, pinpointing SERCA as a key effector of THADA function. In sum, this identifies THADA as a regulator of the balance between energy consumption and energy storage, which was selected during human evolution.